1984
DOI: 10.1021/jm00371a017
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus analogs of .gamma.-aminobutyric acid, a new class of anticonvulsants

Abstract: A series of phosphorus compounds, designed as analogues of gamma-aminobutyric acid (GABA) in that they possess a P = O moiety separated by three atoms from an amino or acetamido group, was synthesized and tested by using in vitro GABAA and GABAB receptor binding, GABA uptake assays, and was examined for anticonvulsant activity. Weak GABAB receptor affinity was noted for one agent, whereas six compounds displayed moderate to high potencies as inhibitors of electroshock- and pentylenetetrazol-induced seizures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…O-Demethylation using Li(s-Bu) 3 BH, as described in Chowdhury et al (2007), followed by hydrogenolytic removal of the Cbz group, afforded the products in 73% [(R)-11] or 60% [(S)-11] yield over the three steps. Finally, 2-aminoethyl benzylphosphonate (12) was synthesized in 55% yield in a single step by reaction of benzylphosphonic acid with aziridine using an adaptation of the procedure described by Cates et al (1984) for preparation of 2-aminoethyl phenylphosphonate (Fig. 2D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O-Demethylation using Li(s-Bu) 3 BH, as described in Chowdhury et al (2007), followed by hydrogenolytic removal of the Cbz group, afforded the products in 73% [(R)-11] or 60% [(S)-11] yield over the three steps. Finally, 2-aminoethyl benzylphosphonate (12) was synthesized in 55% yield in a single step by reaction of benzylphosphonic acid with aziridine using an adaptation of the procedure described by Cates et al (1984) for preparation of 2-aminoethyl phenylphosphonate (Fig. 2D).…”
Section: Resultsmentioning
confidence: 99%
“…Cates et al (1984) showed that 2-aminoethyl phenylphosphonate weakly inhibits the binding of [ 3 H]GABA to GABA A and GABA B receptors in rat brain. Overall however, phosphonic analogs of GABA are much less well characterized, and structure-activity relationships within this class are unknown.…”
Section: Gaba (mentioning
confidence: 99%
“…TPMPA, which is a weaker GABA B agonist than 3-APMPA (Ragozzino et al 1996), had an intermediate effect on the nSTR. Thus, the cyclic tetrahydropyridyl side chain of TPMPA may be needed to attenuate the GABA B R agonism of 3-APMPA, whereas the 2-aminoethoxy side chain of 2- AEMP, which is isosteric to the side chain of 3-APMPA, appears to convey intrinsically weak agonism at GABA B R. Because to date only a few 2-aminoethyl phosphonates have been tested for interaction with GABA receptors (Cates et al 1984; Chowdhury et al 2007; Xie et al 2011), and none have been specifically tested at GABA B R, conclusive testing of the structure-activity properties just noted will require further investigations. Overall, the present and previous evidence for 2-AEMP’s selectivity for GABA C R, together with its ease of synthesis, emphasize the desirability of its further study in the field of GABA C R pharmacology.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal GABA A receptors are less sensitive and are more rapidly desensitized than GABA C R (Cates et al 1984; Eggers and Lukasiewicz 2011; Lukasiewicz and Shields 1998). Activation of retinal GABA A R is likely to have an inhibitory effect on bipolar cell responses, and these receptors likely do not mediate the tonic effects on membrane potential that have been ascribed to GABA C R in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…As a background to the development of phaclofen, we examined the actions of a number of phosphono-analogues of GABA at GABAB-receptors, there being two considerations that prompted our search for antagonists amongst such phosphono-analogues. Firstly, although previously found inactive in the periphery (Muhyaddin et al, 1982), 3-APPA depresses central neuronal activity in a bicuculline-insensitive manner (Curtis & Watkins, 1965;Bioulac et al, 1979), and shows affinity for GABA5-receptors (Cates et al, 1984) suggesting that 3-APPA might be a GABA.-receptor agonist; preliminary investigations showed 3-APPA in fact to be a partial agonist at these receptors ; see also Luzzi et al, 1986 which appeared contemporaneously). Secondly, antagonism is conferred upon glutamate analogues by co-phosphono-substitution (Watkins, 1981), which in turn originally suggested to us that similar analogues of GABA might be antagonists at GABA3-receptors.…”
Section: Introductionmentioning
confidence: 94%